A generalization of contraction principle - K. M. Ghosh (International Journal of Mathematics and Mathematical Sciences)
In this paper, a generalized mean value contraction is introduced. This contraction is an extension of the contractions of earlier researchers and of the generalized mean value non-expansive mapping. Using the generalized mean value contraction, some fixed point theorems are discussed.